2013
DOI: 10.1111/ijcs.12010
|View full text |Cite
|
Sign up to set email alerts
|

A review to inform understanding of the use of food safety messages on food labels

Abstract: Food labels are central for communicating information about food products to consumers, and thus are important for imparting food safety messages, particularly as a high proportion of food‐borne illnesses are caused by poor domestic food handling practices. This paper reviews studies investigating consumers' responses to labels, emphasizing findings related to food safety messages. The evidence is contradictory but consumers do use labels. However, as labels contain so much diverse information it can be diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…The results of surveys confirm the importance of the declaration on the healthful properties of a product in obtaining the acceptance of functional products (Leathwood et al ., ; Williams and Ghosh, ; Williams et al ., ; Pothoulaki and Chryssochoidis, ; Verbeke et al ., ). What is more, the research indicates that consumers attach great importance to the information on the label, such as expiry date, healthful properties and nutritional values (Krystallis et al ., ; Hall and Osses, ).…”
Section: Discussionmentioning
confidence: 97%
“…The results of surveys confirm the importance of the declaration on the healthful properties of a product in obtaining the acceptance of functional products (Leathwood et al ., ; Williams and Ghosh, ; Williams et al ., ; Pothoulaki and Chryssochoidis, ; Verbeke et al ., ). What is more, the research indicates that consumers attach great importance to the information on the label, such as expiry date, healthful properties and nutritional values (Krystallis et al ., ; Hall and Osses, ).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Pieniak, Vanhonacker and Verbeke (2013), investigating the information behavior of fish consumers, found that food labels and employees of food retail stores are frequently used sources. Other studies also confirm that consumers often use food labels-for example, to seek nutrition information (Grunert & Wills, 2007)-despite the fact that, as Wills, Schmidt, Pillo-Blocka, and Cairns (2009) note, nutrition labels are not always effective, especially when they contain a vast amount of diverse information (Hall & Osses, 2013). In general, the effectiveness of nutritional labels is heavily influenced by their format and wording (Hieke & Taylor, 2012); hence, an "inappropriate" form and/or wording can discourage the use of labels as information sources.…”
Section: Downloaded By [Florida International University] At 09:15 27mentioning
confidence: 96%
“…Many of these studies have focused on exploring the determinants of LIS (Drichoutis et al ., ), whereas few studies have created frameworks to explain LIS as part of the decision‐making process [e.g. see (Moorman, ; Szykman et al ., ; Drichoutis et al ., ; Drichoutis et al ., ; Grunert and Wills, ; Hall and Osses, )]. This study contributes to filling this gap.…”
Section: Introductionmentioning
confidence: 99%
“…nutrition labels, environmental labels, warning labels, health claims and so forth. (Juhl and Poulsen, 2000;Baltas, 2001;Cheftel, 2005;Van Trijp and Van der Lans, 2007;Grunert et al, 2010;Hall and Osses, 2013;Beruchashvili et al, 2014). Consequently, food labelling and consumers' label information search (LIS) have emerged as important aspects of the consumer behaviour literature (Drichoutis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%